МЕДИА МАКАНДА МӘЛИМЛЕМЕ ХЫЗМЕТИ ИНФОРМАЦИЯ ЖЕТКЕРИЎШИ ДЕРЕК СЫПАТЫНДА (Konferensiyalar | Conferences, 2023)
Information services in the media space is one of the sources of information communication. Scientific research in each area, statistics, facts and analyzes, described in interaction.